The Scenario of Carbonaceous Aerosols and Total Solar Radiation in Two Cities in Nepal - Sharma, R.K.; Bhattarai, B.K.; Sapkota, B.K.; Gewali, M.B.; Kjeldstad, B. (Journal of Technology Innovations in Renewable Energy, 2017)
Measurement of elemental carbon (EC) and black carbon (BC) aerosols was carried out using AE-31, 7 channel aethalometer at Kathmandu and Biratnagar; two mega cities of Nepal, for five months, January to May 2011 to study its temporal and spatial variation. Total solar radiation was also monitored using Kipp and Zonen CMP 6 pyranometer. Monthly concentration variation for EC and BC was distinct in both study sites. At Biratnagar, monthly EC concentration varies from 3.3 -20.7 µg /m3 while in Kathmandu it varies between 6.0-13.7 µg /m3. Similarly, BC monthly concentration ranges from 3.3 -20.1 µg /m3 and 7.0-14.9 µg /m3 respectively. It was found that both EC and BC were highest during January in both the sites and it decreases gradually. Monthly average solar radiation shows a maximum value in May and minimum in January. A distinct anti-correlation between monthly average carbonaceous aerosols and total solar radiation was observed. Moreover, there was a pronounced diurnal variation of both carbonaceous aerosols EC and BC in the sites with two high peaks one in the morning at about 9:00 and another at late evening 20:00 local time with minimum concentration in the afternoon. The nature of peaks were different at two sites. Biratnagar shows a larger evening peak while Kathmandu shows in the morning inferring heavy domestic and industrial fuel consuming activities in evening and morning respectively. In addition to this, daily and monthly concentration of EC was more than BC at Biratnagar reflecting slightly more biomass fuel consumption than fossil fuel for domestic, industrial and other urban activities. In contrast to this, Kathmandu shows more domination of fossil fuel than biofuel because of reverse order concentration of carbonaceous aerosols. Total solar radiation also shows apparent diurnal variation in both sites with the highest value at around noon time.